Epistemology Of Contemporary Hermeneutics (A Comparative Study between Gadamer and Derrida): Epistemologi Hermeneutika Kontemporer (Studi Perbandingan antara Gadamer dan Derrida) - Nurullaila, Azzah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Hermeneutics, as the philosophy of interpretation, plays a pivotal role in understanding texts across disciplines, from theology to cultural studies. Specific Background: Hans-Georg Gadamer and Jacques Derrida stand as two influential yet contrasting figures in this tradition, with Gadamer emphasizing dialogue, tradition, and historicity, while Derrida underscores différance, instability of meaning, and deconstruction. Knowledge Gap: Despite their profound influence, comparative epistemological analysis of their methods, particularly in relation to interdisciplinary applications such as Islamic studies, remains underexplored. Aims: This study aims to examine and compare Gadamer’s philosophical hermeneutics and Derrida’s deconstructive approach, highlighting their epistemological implications and potential contributions to modern interpretation. Results: The findings reveal that Gadamer’s model fosters historically grounded dialogue through the fusion of horizons, while Derrida’s deconstruction opens interpretive spaces by exposing contradictions and indeterminacies within texts. Novelty: By placing these two thinkers in direct comparison, this research demonstrates how their divergent approaches can complement one another, offering both contextual depth and critical reflexivity in interpretation. Implications: The study provides a theoretical and practical framework for applying hermeneutics in philosophy, humanities, and religious studies, advocating a more inclusive, dynamic, and critical interpretive practice suitable for addressing contemporary academic and societal challenges.Highlight : Gadamer emphasizes tradition, history, and dialogue in the process of understanding texts. Derrida reveals the instability of meaning through the method of deconstruction. Both contribute significantly to the development of contemporary hermeneutics Keywords : Comparative, Hermeneutics, Hans-Georg Gadamer, Jacques Derrida, Epistemology3